The Psychometric Properties of the Norwegian version of Kinder Lebensqualität Fragebogen (KINDL®) - Jozefiak, Thomas; Reinfjell, Trude (PsykTestBarn, 2012)
Description: The original German Kinder Lebensqualität Fragebogen (KINDL®) was published in 2000. It was translated into Norwegian, following international guidelines, in 2004. For copyright see www.KINDL.org. The KINDL® is a questionnaire that measures quality of life, and has four versions: a self-report version for children aged 8-12; a self-report version for adolescents aged 13-16; a parent-proxy version for children aged 4-7; and a parent-proxy version for children and youths aged 8-16. Six subscales each with 4 items (Physical and Emotional Well-being, Self-esteem, Family, Friends and School) and one total scale (24 items) can be calculated. The parent-proxy version for children aged 4-7 has only one 12-item total scale. Completion time is less than 30 minutes. Scoring is performed by using a SPSS syntax. For interpretation and scoring a 3-year higher education in health or social studies is required. Literature search: We found 7 Norwegian publications, (3 based on the same convenience sample of 9 graders in Oslo). Two studies reported on representative data from the general and two from clinical populations. Psychometrics: Only one study reported norm data. The KINDL® showed satisfactory to good internal consistency reliability, except for some subscales for the youngest children. Good test-retest reliability was found, except for one subscale. Construct validity has not been documented. Conclusion: KINDL® is a promising instrument. For clinical decision making we recommend using only the total scales. There exists no psychometric documentation for the parent-proxy version for children aged 4-7.